PENGARUH KOMUNIKASI DAN PELAYANAN DIVISIINFORMASI TERHADAP KEPUASAN PASIEN DI RS BHAYANGKARA TK. I PUSDOKKES POLRI - Oka Murti, Rizky; asim, asim (JURNAL ADMINISTRASI & MANAJEMEN, 2025)
Hospitals are institutions that operate in the field of services, especially health, and play an important role in society. Therefore, the public demands high levels of pressure on hospitals to provide good service so that patient satisfaction can be felt. This research aims to analyze and explain the influence of Human Resources in communicating when providing services to the community. This research was conducted at the Bhayngkara Tk.I Hospital, Pusdokkes Polri Jakarta. This research uses quantitative methods with the technique taken, namely accidental sampling by distributing questionnaires to obtain data that will be processed in SPSS. The total sample was 155 respondents. The results of this research: Communication has a positive and significant effect on Patient Satisfaction, Service has a positive and significant effect on Patient Satisfaction, and Communication has a positive and significant effect on Service. Bhayangkara Hospital Tk.I Pusdokkes Polri can improve communication infrastructure and utilize information technology and collaborate with other divisions so that the information conveyed is consistent. Keywords : Communication, Service, Patient Satisfaction